The Impact of Silver Nanoparticles on Dentinal Tubule Penetration of Endodontic Bioceramic Sealer - Sundus Bukhary; Sarah Alkahtany; Amal Almohaimede; Nourah Alkhayatt; Shahad Alsulaiman; Salma Alohali (Applied Sciences)
The impact of adding silver nanoparticles (AgNPs) to bioceramic (BC) sealer on their ability to penetrate dentinal tubules is still unknown. Thus, this confocal laser scanning microscopic (CLSM) study aimed to assess the extent of dentinal tubule penetration of BC sealer (TotalFill® Hiflow BC Sealer™, FKG, Switzerland) with and without AgNPs using the single-cone (SC) technique and the continuous-wave condensation (CWC) technique. AgNPs alone as well as in a mixture with the BC sealer were characterized using scanning electron microscopy and transmission electron microscopy. Single-rooted extracted human teeth (N = 100) were selected and prepared, and then divided into four groups (n = 25). Group 1 (BC/SC): BC sealer obturated with the SC technique. Group 2 (BC+AgNPs/SC): BC sealer with AgNPs obturated with the SC technique. Group 3 (BC/CWC): BC Sealer obturated with the CWC technique. Group 4 (BC+AgNPs/CWC): BC Sealer with AgNPs obturated with the CWC technique. After 2 weeks, roots were horizontally sectioned to obtain 1 mm thick dentin slices that were evaluated with CLSM. Sealer dentinal tubule penetration area and the maximum depth of penetration were measured. Data were analyzed with one-way ANOVA and the Tukey multiple comparison tests (p ≤ 0.05). The characterization process demonstrated a spherical-shaped nanoparticles without obvious agglomeration. The results showed that Group 2 (BC+AgNPs/SC) significantly demonstrated the highest mean tubular penetration depth, while group 3 (BC/CWC) had the lowest mean depth. Group 2 (BC+AgNPs/SC) exhibited the significantly highest mean value for the total area of penetration. However, groups 1 (BC/SC) and 3 (BC/CWC) exhibited the lowest mean value of total penetration area, with no statistically significant difference. The integration of AgNPs with BC sealer markedly enhanced penetration into dentinal tubules. The SC technique demonstrated superior penetration relative to the CWC technique.